Ciddi Pulmoner Hipertansiyonlu Komplet Atriyoventriküler Kanal Defekti Onarımından Sonra Kombine İnhale Nitrik Oksit ve Oral Sildenafil Kullanılması: Vaka Sunumu ve Literature Taraması - (:unkn) unknown (My University, 2017)
Amaç: Down sendromu ve komplet tip atrioventriküler septal defekt (KAVSD) tanılarıyla takip edilen 12 aylık erkek hasta tam düzeltme operasyonu sonrası postoperatif dönemde pulmoner hipertansif kriz yaşadı. Pulmoner hipertansif kriz inhale nitrik oksit (iNO) tedavisi ile (40-60 ppm) başarılı bir şekilde kontrol edildi. Takiplerinde methemoglobinemi gelişen hastada iNO dozu 24 saat sonra azaltılmak zorunda kalındı (10 ppm). Tedaviye sildenafil tablet (6 mg/kg/gün) eklenmesi ile postoperatif pulmoner hipertansif krizler kontrol altına alındı. Konjenital kalp cerrahisinde pulmoner hipertansif krizlerin engellenmesinde ve yan etkilerin kontrol edilmesinde kombine tedaviler etkili yöntemlerdir.

Objective:A 12 month old male baby with diagnoses of Down syndrome and complete atrioventricular canal defect underwent total correction. His early postoperative course was complicated with pulmonary hypertensive crises. It was initially treated by 40-60 ppm inhaled nitric oxide (iNO), but we had to decrease the dosage because of serum increased methemoglobin levels after 24 hours of treatment (10 ppm). We added oral sildenafil sitrate as a combination therapy (6 mg/kg/day) which was seemed to be effective in controlling pulmonary hypertensive crises. Combined regimens like iNO and sildenafil for postoperative pulmonary hypertensive crises are beneficial in terms of reducing the dosage of iNO and preventing rebound pulmonary hypertension.
Combined Use Of İnhaled Nitric Oxide and Oral Sildenafil After Repair of Complete Atrioventricular Canal Defect with Severe Pulmonary Hypertension: Report of A Case And Review of Literature
Keywords: Kalp ve Kalp Damar Sistemi